Nephrogenic systemic fibrosis/nephrogenic fibrosing dermopathy: A decade-old disease - Panda Saumya (Wolters Kluwer Medknow Publications, 2007)
Nephrogenic systemic fibrosis, also known as nephrogenic fibrosing dermopathy, is a rare fibrosing disorder of skin and internal organs that occurs in the context of renal insufficiency, particularly in those who have undergone dialysis. It was first described in 1997 in the United States. The first non Western series was reported from Kolkata, India in 2005 the etiology is unknown. High-dose erythropoietin and use of gadolinium-containing contrast media are currently acknowledged to be important risk factors. The pathogenesis is multifactorial. The current hypothesis supports the role of circulating fibroblast precursors (fibrocytes) and the elaboration of circulating fibrogenic factors ( e.g., transforming growth factor beta 1). The clinical characteristics resemble scleromyxedema with a typical distribution pattern of its own. The histopathological hallmarks are spindle-shaped cells in the background of dermal fibrosis and deposition of collagen and mucin. Dual immunolabelling with CD34 and procollagen is diagnostic. There are no standard, specific and universally satisfactory treatments. The natural history is progressive with systemic manifestations conferring a poor outcome.